Gender-Based Violence and Associated Factors Among Women with Disabilities in Jimma Town, Ethiopia - Getachew S; Debelew GT; Abdullahi M (Dove Medical Press, 2022)
Selamawit Getachew,1 Gurmesa Tura Debelew,2 Misra Abdullahi2 1Department of Public Health, Wachemo University, Hosanna, Ethiopia; 2Department of Population and Family Health, Faculty of Public Health, Jimma University, Jimma, EthiopiaCorrespondence: Selamawit Getachew, Department of Public Health, Wachemo University, Hosanna, Ethiopia, Email selamgetachew900@gmail.comBackground: Globally, women with disabilities have two times higher chance of suffering from violence compared to their non-disabled peers due to double discrimination. However, there is little evidence that quantifies the situation in this segment of the population by considering disability-related factors which make this group more vulnerable to gender-based violence in Ethiopia.Objective: To assess the prevalence of gender-based violence and its associated factors among women with disabilities in Jimma town, southwest Ethiopia, 2020.Methods: A community based cross-sectional study was conducted among a total of 308 women with disabilities. Bivariate and multivariable logistic regression analyses were carried out to identify factors associated with gender-based violence. The significance of the association was decided by using the 95% confidence interval of AOR at a p-value of < 0.05 in the multivariable analysis.Results: The lifetime prevalence of gender-based violence among women with disabilities was found to be 73.1, while 46.1% had experienced it during the last 12 months. Gender-based violence in the past 12 months was significantly associated with non-schooling (AOR=5.10; 95% CI, 1.51, 17.14), being in age group of 20- 34 (AOR=3.5; 95% CI, 1.74, 7.30), having visual impairment (AOR=3.1; 95% CI, 1.27, 7.54), having hearing impairment (AOR=3.0; 95% CI, 1.36, 6.89), alcohol use behavior (AOR=4.1; 95% CI, 1.74, 9.55), and perceived stigma and discrimination (AOR=4.2; 95% CI, 2.44, 7.39).Conclusion: Prevalence of gender-based violence among women with disabilities was found to be high in the study area. Educational status, age, type of disability, alcohol use behavior, and perceived stigma and discrimination were independent predictors of gender-based violence. Measures have to be taken to curb the problem by taking integrated interventions like enrolling girls in school and targeted health education towards identified factors by considering the heterogeneity of disabilities.Keywords: gender-based violence, violence against women, disability, southwest Ethiopia